Liver R2* is affected by both iron and fat: A dual biopsy‐validated study of chronic liver disease. Issue 1 (13th January 2019) - Karlsson, Markus; Ekstedt, Mattias; Dahlström, Nils; Forsgren, Mikael F.; Ignatova, Simone; Norén, Bengt; Dahlqvist Leinhard, Olof; Kechagias, Stergios; Lundberg, Peter
Abstract : Background: Liver iron content (LIC) in chronic liver disease (CLD) is currently determined by performing an invasive liver biopsy. MRI using R2* relaxometry is a noninvasive alternative for estimating LIC. Fat accumulation in the liver, or proton density fat fraction (PDFF), may be a possible confounder of R2* measurements. Previous studies of the effect of PDFF on R2* have not used quantitative LIC measurement. Purpose: To assess the associations between R2*, LIC, PDFF, and liver histology in patients with suspected CLD. Study Type: Prospective. Population: Eighty‐one patients with suspected CLD. Field Strength/Sequence: 1.5 T. Multiecho turbo field echo to quantify R2*. PRESS MRS to quantify PDFF. Assessment: Each patient underwent an MR examination, followed by two needle biopsies immediately following the MR examination. The first biopsy was used for conventional histological assessment of LIC, whereas the second biopsy was used to quantitatively measure LIC using mass spectrometry. R2* was correlated with both LIC and PDFF. A correction for the influence of fat on R2* was calculated. Statistical Tests: Pearson correlation, linear regression, and area under the receiver operating curve. Results: There was a positive linear correlation between R2* and PDFF (R = 0.69), after removing data from patients with elevated iron levels, as defined by LIC. R2*, corrected for PDFF, was the best method for identifying patients with elevated iron levels, with a correlation of R = 0.87 and a sensitivity and specificity of 87.5% and 98.6%, respectively. Data Conclusion: PDFF increases R2*. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:325–333.